Assessment of wheat variety distinctness using SSR markers - Li-xin WANG; Jun QIU; Li-fang CHANG; Li-hua LIU; Hong-bo LI; Bin-shuang PANG; Chang-ping ZHAO (Journal of Integrative Agriculture, 2015)
Assessment of variety distinctness is important for both the registration and the protection of particular variety. However, the current testing system, which assesses a range of morphological characters of each pair of varieties grown side-by-side, is time-consuming and is not suitable for the assessment of hundreds of samples. The objective of this study was to develop a procedure for the assessment of wheat variety distinctness using simple sequence repeat (SSR) markers. A comparison between the molecular and morphological profile of 797 varieties was made. On the basis of the comparison, pairs of varieties with a genetic similarity value (GSV) ≤90% were deemed to be distinct, accounting for ∼85% of varieties assessed in wheat regional trials. For the remaining ∼15% of varieties, GSVs between different varieties were >90%, among which ∼35% were not distinct and the other ∼65% were distinct. Therefore, if given a GSV>90%, the pairs of varieties should be morphologically assessed in the field. To avoid any errors in the assessments, we proposed the elimination of contaminant plants from the sample before comparing the varietal genotypes, scoring of the genotype at each locus with a pair of allele numbers when constructing a molecular profile, and faithfully recording two alleles at a non-homozygous locus. To reduce the workload and cost, a three-grade markers comparison among varieties is suggested. In addition, 80 SSR markers and a technical procedure for assessment of wheat variety distinctness have been proposed. Based on the procedure, the distinctness assessment of ∼85% of all wheat varieties is completed in our laboratory annually. Consequently, total field assessment has been reduced considerably.